Gaps in governance of process-oriented credence attributes: the South African free-range dairy dilemma - Serebro, Danielle (My University, 2016)
This study investigates the nature of labelling and regulation in South African free-range dairy production. It aims to reveal the complexities of designing and implementing regulation on process characteristics and policy’s failure to address the heterogeneous needs of consumers and producers. In parallel, the tensions that arise in the policy-production interaction are considered. This research addresses a gap in the theoretical and industry literature regarding understanding and explaining labelling, certification and regulation of credence attributes, such as animal welfare, within food systems. It provides interesting and important insight into regulation’s role in developing alternative production structures and niche markets as a response to variety in consumers’ needs and tastes. It is therefore relevant more broadly for understanding drivers for and governance of other niche production structures such as organic, fair-trade and religious or cultural influences.
Research report submitted in partial fulfillment of the requirements for the degree Master of Commerce in Development Theory and Policy at The University of the Witwatersrand 2016
Keywords: Dairying--Production control--South Africa.; Animal welfare--South Africa; Consumers' preferences--South Africa